Tissue Specific Localization of Several Oil Palm Genes During Flower Development - Rahmat, Zaidah (2001)
Flowering is the first introductory step to fruit formation and is a fundamental part of the plants reproduction system. Flowers and fruit are also an integral part of seed production. In most crops, the control of flowering is an important aspect of growth and development. If oil palm flowering could be controlled, yield could be improved by stimulating flowering in accordance to permissive environmental factors. In order to determine the factors that influence flowering of oil palm, the physiological background and the flowering process must be studied. However, oil palm micropropagation had come up against a major difficulty with the discovery of a floral morphogenesis abnormality induced by in vitro regeneration (Corley et al., 1986; Toruan-Mathius et al., 1998). From the examination of both morphology and anatomy of oil palm flower development, 9 key stages of normal and abnormal flower development has been classified to assist in the study of tissue specific expression of flowering genes. As plant organ systems are composed of anatomically similar cells and tissues, in situ hybridization was chosen as a method of determining gene expression based on its sensitivity and ability to determine the specific location of an mRNA. Examinations carried out on 4 oil palm flowering genes provide more information about the processes occurring during normal and abnormal flower formation of oil palm. OPSOC1, an oil palm homologue of AGL20 and OPLFY, the LFY homologue of oil palm, are both expressed throughout flower initiation and development. OPRLK5, a member of the receptor kinase gene family, is expressed throughout flower development. The last gene, OPUIP2, which encodes a UFO-interacting protein, is also expressed throughout flower development but it is not needed during inflorescence meristem development. Combined with other studies in this area, it is hoped that an understanding of the floral abnormality may be within reach in the near future. Attempts to isolate flower specific genes from an oil palm floral cDNA library however have been unsuccessful. The choice of cDNA library and conventional molecular tools might not be applicable in isolating these types of genes. Nevertheless, with advanced molecular and genetic tools such as yeast one and two-hybrid system that are being developed, isolation and the determination of function of such genes can be achieved.